Identifikasi Bahaya dan Penilaian Risiko Keselamatan dan Kesehatan Kerja Menggunakan Metode HIRARC pada Perusahaan Makanan - Jordan Gustav; Ayu Prima Kartika; Rici Riansyah; Afrian Eskartya Harjono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Occupational safety and health (OSH) is an important aspect in creating a safe working environment, especially in the food industry which has various work hazards. This study aimed to identify hazards, assess risk levels, and determine risk control measures using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method in the production area of PT. X. This research used a descriptive qualitative method with an observational approach through observation, interviews, and documentation. Risk assessment was carried out using a risk matrix based on ANSI Z10-2005 standards by determining the likelihood and severity values of each identified hazard. The results showed that the hazards found included mechanical, physical, ergonomic, and chemical hazards. The highest risk was found in machine operation activities with a risk value of 20 categorized as extreme risk. Other risks included hands caught in machines, exposure to hot temperatures, slippery floors, manual handling activities, and workers not using personal protective equipment (PPE) properly. Recommended risk controls include installing machine guards, improving workplace conditions, providing material handling aids, and conducting regular OSH training.